Global Trends and Transformative Insights in Artificial Intelligence (AI) Research: A Bibliometric Analysis of the Dynamics of Education, Ethics, and Innovation - Rinta Anisaturrizqi; Rina Rifky Yulianti (Indonesian Journal of Progressive Pedagogy, 2025)
Artificial intelligence (AI) research has grown significantly in the last decade, playing a crucial role in education, healthcare, and industry. This study explores global AI research trends using a bibliometric approach, analyzing geographical contributions, key themes, and temporal dynamics. Keyword network visualization highlights dominant themes such as “machine learning,” “digital transformation,” and “ethical AI,” along with their interconnections reflecting AI's evolution. The United States leads with 38% of global AI publications, followed by China and India, reinforcing their roles as innovation hubs. Leading institutions, including the University of California and Beijing Normal University, significantly contribute to machine learning and generative AI research. A surge in AI publications in 2023 indicates the growing influence of generative tools like ChatGPT. This study enriches the literature on AI trends while providing insights for policymakers to guide research investments. Understanding inter-topic relationships and cross-country collaborations offers new interdisciplinary and international cooperation opportunities. The findings provide a comprehensive AI research map to guide future studies and technological advancements.